Electronic Word Of Mouth Dan Brand Image Dalam Minat Beli Layanan Aplikasi Musik Spotify - Reynanta Masdaner; Poppy Ruliana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
Currently the trend of listening to music using music application is gaining popularity. One of the most popular streaming music applications is Spotify. Spotify’s strong brand image makes it easy for the public to remember. Spotify’s brand image was formed through electronic word of mouth (eWOM). eWOM is marketing communication strategy that influences and generates buying interest when users see interesting and positive comments on the internet regarding the Spotify streaming music application product. This study aimsto determine the effect of eWOM and brand image on interest in purchasing Spotify premium services. What is meant by premium service is a paid feature to get full and ad free access. This study uses a quantitative approach using a survey method which conducted on 100 students of STIKOM Interstudi who are users of the Spotify streaming music application. The results show that eWOM and brand image have a positive influence on the interest in buying premium services for the Spotify streaming music application